2012
DOI: 10.1124/jpet.112.198499
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Butyrylcholinesterase Organophosphate-Resistant Variants through a Novel Mammalian Enzyme Functional Screen

Abstract: Human butyrylcholinesterase (hBChE) is currently being developed as a detoxication enzyme for the catalytic hydrolysis or stoichiometric binding of organophosphates (OPs). Previously, rationally designed hBChE mutants (G117H and E197Q) were reported in the literature and showed the feasibility of engineering OP hydrolytic functional activity into hBChE. However, the OP hydrolysis rate for G117H is too low for clinical utility. Additional OP-resistant hBChE variants with greater hydrolysis rates are needed as O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…However, its reaction with nerve agents requires some improvement as it is inactivated when it complexes with the substrate. Rational design yielded variants with slightly increased resistance to OPs but with reduced catalytic efficiency (Zhang et al, 2012a). However, evolution of this same enzyme with nerve agent analogues identified three variants with increased resistance to these compounds while retaining high catalytic efficiency.…”
Section: Enzyme Bioremediationmentioning
confidence: 99%
“…However, its reaction with nerve agents requires some improvement as it is inactivated when it complexes with the substrate. Rational design yielded variants with slightly increased resistance to OPs but with reduced catalytic efficiency (Zhang et al, 2012a). However, evolution of this same enzyme with nerve agent analogues identified three variants with increased resistance to these compounds while retaining high catalytic efficiency.…”
Section: Enzyme Bioremediationmentioning
confidence: 99%
“…Using a novel adenovirus-mediated mammalian BChE functional screen approach, our group identified several variants including G117R, G117N, E197C, and L125V that showed promising enzyme kinetics in OP resistance [94]. Although the physiological function of BChE is still not clear, it has been shown that exogenously administered BChE provides effective protection against OP exposure.…”
Section: Bche Variant Approachesmentioning
confidence: 99%
“…The inhibitory activity was measured by a spectrophotometric method 15 . The reaction mixture contained 190µl Trizma buffer (100mM) (pH 8.0), 20µl of the sample and 40µl of butyrylcholinesterase solution (0.035U/ml) were mixed and incubated for 30min (4 °C).…”
Section: Butyrylcholinesterase Inhibition Assaymentioning
confidence: 99%